Null geodesics and observables around the Kerr–Sen black hole. (15th December 2017) - Uniyal, Rashmi; Nandan, Hemwati; Purohit, K D
Abstract: We investigate the geodesic motion in the background of the Kerr–Sen black hole arising in heterotic string theory. The nature of the effective potential is discussed in the radial, as well as latitudinal, direction. A special class of spherical photon orbits is obtained along with an expression for the turning point for the radial photons. Dependence of photon motion within this class of solution is discussed explicitly in view of the different black hole parameters. We have discussed the allowed regions for the geodesic motion of massless test particles around the Kerr–Sen black hole in a more generalised way by considering non-equatorial motion of the photons into account. The conditions for different types of possible orbits are discussed with specific parameter values along with the corresponding orbit structure. No terminating orbits are possible for photons due to non-zero black hole charge. Observables on the angular plane (viz. bending of light and perihelion precession for massive test particles) are analysed as special cases. We have also calculated the rotation and mass parameters for the Kerr–Sen black hole in terms of the red/blue shifts of the photons in circular and equatorial orbits emitted by the massive test particles which represent stars or other probable sources of photons.